The Effect of the Complex Instruction Learning Model on High Jump Learning Outcomes Among Students of SD Negeri 071132 Bintuang in the 2022/2023 Academic Year - Hondro, Faluazisokhi; Sari, Liliana Puspa; M, Benny Aprial (Educational Sciences Journal, 2025)
This study aimed to determine the effectiveness of the Complex Instruction learning model in improving students’ learning outcomes in the high jump subject at SD Negeri 071132 Bintuang, Pulau-Pulau Batu Barat District, South Nias Regency, during the 2022/2023 academic year. The Complex Instruction model emphasizes collaboration, communication, and social interaction within heterogeneous student groups to foster equitable participation and mutual learning. This research applied a Classroom Action Research (CAR) design consisting of two cycles, each including stages of planning, action, observation, and reflection. Data were collected using psychomotor assessment instruments focusing on the students’ high jump performance. The initial results showed that only one out of nineteen students (5.2%) met the minimum mastery criterion. After implementing the Complex Instruction model, the results improved, with 26.3% achieving mastery in Cycle I and 36.8% in Cycle II. The average score increased from 42.1 in the pre-test to 60.8 in Cycle II. The findings indicate that the Complex Instruction model can enhance student learning outcomes in the high jump, particularly among upper-grade students (grades 5 and 6) who demonstrated 100% mastery. It is recommended that this cooperative learning approach be applied primarily to upper elementary students who have developed sufficient physical and motor readiness to perform the required jumping and landing techniques effectively.